Lower socioeconomic status, adiposity and negative health behaviours in youth: a cross-sectional observational study. Issue 5 (18th May 2015) - Lord, Sarah; Manlhiot, Cedric; Tyrrell, Pascal N; Dobbin, Stafford; Gibson, Don; Chahal, Nita; Stearne, Karen; Fisher, Amanda; McCrindle, Brian W
Abstract : Objective: Understanding obesity and its modifiable risk factors in youth is key to addressing the burden of cardiovascular disease later in life. Our aim was to examine the associations among adiposity, negative health behaviours and socioeconomic status in youth from the Niagara Region. Design, setting and participants: Cross-sectional observational study of 3467 grade 9 students during their mandatory health and physical education class to investigate the association between socioeconomic status (postal code), self-reported health behaviour and adiposity in the Niagara Region, Ontario, Canada. Results: Median household income was 63 696 and overall percentage below the after-tax low-income cut-off was 4.2%. Negative health behaviours (especially skipped meals, lower fruit and vegetable consumption, higher screen time) were associated with lower income neighbourhoods, however, the absolute effect was small. Those participants in the lowest income quintile had a significantly greater body mass index z-score than those in the highest (0.72±1.19 vs 0.53±1.12), but the overall trend across quintiles was not statistically significant. A similar trend was noted for waist-to-height ratio. The lowest income neighbourhoods according to after-tax low-income cut-off had small but statistically significant associations with higher adiposity compared with the middle or highest income neighbourhoods. Conclusions: Obesity prevention efforts should target modifiable behaviours, with particular attention to adolescents from lower income families and neighbourhoods.